Results of the pioneer survey of potential bat hibernacula in Albania (2012–2015) - Philippe Théou; Ervis Loce; Marina Đurović (Natura Sloveniae)
For the first time at a national scale in Albania, a winter bat population census in potential hibernacula has been implemented during the four winters (early 2012, 2012/2013, 2013/2014 and 2014/15). 178 potential hibernation sites have been visited. During the visits of natural caves, bunkers, tunnels, buildings and mines we recorded at least 9 bat species: Rhinolophus ferrumequinum (28 sites), R. hipposideros (36 sites), R. blasii (1 site), R. euryale (3 sites), Myotis myotis/oxygnatus (blythii) (4 sites), M. capaccinii (6 sites), Pipistrellus sp. (2 sites), Hypsugo savii (1 site) and Miniopterus schreibersii (9 sites). The data presented are substantial additions to knowledge on the distribution of these species and their roosts in Albania, and will form a basis for bat population monitoring and, at the same time, for improving conservation measures in Albania and the wider region.